Evaluation of CARPET hardware and software potentialities - Morzabaev A.K.; Giniyatova Sh.G.; Shakhanova G.A.; Makhmutov V.S. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
This article describes the ground-based cosmophysical complex CARPET/ASTANA. The Cosmophysical Complex CARPET/ASTANA was put into operation at the Physico-Technical Faculty of the L.N.Gumilyov ENU. This is software and hardware complex, which includes a CARPET detector, as well as the EFM-100 fluxmeter. The purpose of the installation of the CARPET complex is the measurement and processing of solar and geophysical parameters in the Earth's atmosphere. The CARPET detector detects soft (electronphoton) and hard (muon) components of cosmic rays. Monitoring of the electric field of the atmosphere was carried out using an electrostatic fluxmeter. The processing and analysis of the experimental data of the detector and the fluxmeter allow to carry out investigations of the radiation situation in the earth's atmosphere during flares on the Sun, to measure the maximum intensity of the flux of solar cosmic rays and their energy spectrum. From the analysis of the obtained results, it is concluded that the cosmophysical complex makes it possible to make an assessment of the radiation and meteorological situation in the terrestrial conditions of the region of Astana.
CARPET бағдарламалы-аппараттық кешені мүмкіндіктерін бағалау
Оценка возможностей программно-аппаратного комплекса CARPET
Keywords: secondary cosmic rays; CARPET detector; electrostatic fluxmeter; gas discharge counters